PENINGKATAN KETERCAPAIAN PEMBELAJARAN FIQH DI SMA DENGAN METODE BLENDED LEARNING - Irfan, Lukman; Amri, Khairul; Suratingsih, Suratingsih; Andriani, Ulfa (EL-TARBAWI, 2017)
This paper focuses on fiqh (Islamic jurisprudence) learning at the high school level. The aim of the research is to measure the extent to which the achievement of fiqh learning at the high school level can be improved with the blended learning method. Concept analysis method is used to understand the concept of blended learning and explain its implementation in the field. This research is a class action research which refers to the Kemmis model consisting of four components namely planning, implementation, observation and reflection. It is expected that the blended learning method can improve the achievement of fiqh learning at the high school level. The research found that in the first phase of classroom action research, students have not been able to adjust themselves to learning using the blended learning method, especially with the Kahoot application. Most students are still fixated on conventional learning. Basically, however, the blended learning method can generate high attractiveness for students. Enthusiasm and focus on learning become higher. The feedback obtained shows that 100% of students claim to have learned something, 100% recommend it to be reused and 80% welcome this method with fun. The study suggests that the composition in the placement between direct communication with face to face and online must be appropriate, so that an improvement in fiqh learning can be achieved.Â Keywords: blended learning, fiqh learning, learning outcome